Changing course : blueprint for peace in Central America and the Caribbean (Institute for Policy Studies Washington, DCUS, 1984)
Reviews social and political conditions that underlie current conflicts in the region. Evaluates the threat posed by struggles in Central America to the economic and military security of the USA. Identifies true interests of the USA and points to their misrepresentation by the Reagan administration and others. Outlines characteristics of a new policy to promote peace in the individual Central American territories and in the Caribbean. Outlines program designed to promote long term stability and economic development in the region. Appendicies describe US economic interest in the region; and discusses inter alia, the Kissinger Commission's report.
Includes bibliographical references